Sistem Monitoring Daya Tahan Baterai Backup untuk BTS PT Indosat (Information Technology and Telematics, 2015)
Abstract-- Lifetime Backup Battery Monitoring System for Base Transceiver Station (BTS) PT Indosat in Semarang area is a web based application designed with UML, using MYSQL database with PHPMyAdmin for database administration tools, and GUI (Graphical User Interface) designed using Node.js and PHP. Lifetime Battery Backup Monitoring System used for facilitate Indosat’s technician team to monitor the stability and performance of lifetime backup battery on Indosat’s base transceiver stations in Semarang area, to obtain maximum performance and stability of the base stations for providing best network quality for the customers . This web application will be installed on a server that is connected to the internal network of Indosat Semarang, and does not have a public IP address, so that only certain users of Indosat Semarang technician team who has the right of access to the internal network Indosat Semarang can access this web application. So that other users who do not have the right of access to the internal network Indosat Semarang can not access this web application. Users can access this web application to go directly to the IP address of the web server. Key words: Battery backup, Web monitoring, Nodejs, Mysql, Provider